Premorbid Personality Characteristics in Alzheimer’s Disease: An Exploratory Case–Control Study - M. Malinchoc; W. A. Rocca; R. C. Colligan; K. P. Offord; E. Kokmen (Behavioural Neurology)
Linking data from a case–control study of Alzheimer’s disease with data from a Minnesota Multiphasic Personality Inventory (MMPI) outpatient study, we identified 13 Alzheimer's disease cases and 16 controls for case–control comparison. The mean time between personality testing and onset of Alzheimer's disease (or corresponding age for controls) was 13 years in cases and 14 years in controls. Alzheimer's disease cases, but not the controls, had scores significantly greater than the normative reference on MMPI scales measuring Social Introversion (p = 0.05), and Pessimism (p = 0.01). When compared to controls, Alzheimer's disease cases had significantly greater scores on the Social Introversion scale (p = 0.03). Despite the small sample size and some design limitations of this exploratory study, our findings may suggest that subjects who score higher on these personality scales have a greater risk of Alzheimer's disease.